Cytokinin and gibberellin influence growth and development of Cattleya guttata Lindl. (Orchidaceae) in vitro seedlings - Schuffner, Marco Aurelio Ribeiro; Costa Junior, Otalício Damásio da; Bueno, Luís Henrique; Ladeira, Josimar dos Santos; Oliveira, Lucilene Silva de; Silva, Maurecilne Lemes da; Rocha, Diego Ismael (Ornamental Horticulture, 2026)
Few studies have investigated the effects of plant growth regulators (PGRs) on the development of native Brazilian orchids threatened with extinction and with high ornamental potential, such as Cattleya guttata Lindl. The present study aimed to investigate the effects of cytokinin and gibberellin on the early development of Cattleya guttata seedlings grown in vitro. Seedlings 120-days-old were cultured in MS medium supplemented with either 6-benzyladenine (BA; 4.44 μmol L-1 ), gibberellic acid 3 (GA; 2.89 μmol L-1 ), paclobutrazol (PBZ; 0.85 μmol L-1 ), and BA+GA (BA: GA), or BA+PBZ (BA: PBZ) at the same concentrations. The control treatment consisted of MS medium without PGRs. After 140 days of in vitro growth, seedling development and leaf size and shape were assessed. BA supplementation significantly increased the formation of axillary shoots, resulting in modified seedling architecture. However, the simultaneous application of GA attenuated the effects of BA. Both BA and GA, whether applied individually or together, suppressed root development. When PBZ was added to the medium alone or in combination with BA, the root parameters were like the control. PBZ in the medium affected leaf morphology. BA and PBZ together produced a negative correlation between leaf width and length-width ratio. This study clarifies how cytokinin-gibberellin interactions affects in vitro growth and early development in this ornamental plant species.